Answer:
D. 673 if the functions are f(x)=4x^2-3 and g(x)=5x-2
Explanation:
f(g(3)) is what we need to find.
We start with the inside first: g(3).
g(3) means to take the expression labeled g and replace the input, the x, with 3:
5(3)-2
15-2
13
So g(3) is 13.
Let's go back to finding f(g(3)):
f(g(3))
f(13) :I replaced g(3) with 13.
f(13) means to use the expression labeled f and plug in 13 for the input, x:
4(13)^2-3
4(169)-3
676 -3
673
So f(13) is 673.
Let's go back to the problem one more time:
f(g(3))=f(13)=673.